2021
DOI: 10.3390/fermentation7030117
|View full text |Cite
|
Sign up to set email alerts
|

Smart Detection of Faults in Beers Using Near-Infrared Spectroscopy, a Low-Cost Electronic Nose and Artificial Intelligence

Abstract: Early detection of beer faults is an important assessment in the brewing process to secure a high-quality product and consumer acceptability. This study proposed an integrated AI system for smart detection of beer faults based on the comparison of near-infrared spectroscopy (NIR) and a newly developed electronic nose (e-nose) using machine learning modelling. For these purposes, a commercial larger beer was used as a base prototype, which was spiked with 18 common beer faults plus the control aroma. The 19 aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Six classification ML models for each type of wine were developed using artificial neural networks. As described in previous publications from Gonzalez Viejo et al [ 15 , 33 ], a customized Matlab ® R2021a code developed by the DAFW-UoM group was used to train the models using 17 supervised algorithms classified as two algorithms based on backpropagation with Jacobian derivatives, 11 based on backpropagation with gradient derivatives and four using weight/bias training functions. The best models were selected based on the highest accuracy and performance calculated using means squared error (MSE) to assess the absence of overfitting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six classification ML models for each type of wine were developed using artificial neural networks. As described in previous publications from Gonzalez Viejo et al [ 15 , 33 ], a customized Matlab ® R2021a code developed by the DAFW-UoM group was used to train the models using 17 supervised algorithms classified as two algorithms based on backpropagation with Jacobian derivatives, 11 based on backpropagation with gradient derivatives and four using weight/bias training functions. The best models were selected based on the highest accuracy and performance calculated using means squared error (MSE) to assess the absence of overfitting.…”
Section: Methodsmentioning
confidence: 99%
“…Implementing these digital technologies was the first attempt to transform the grape and wine industry production from traditionally reactive to a more predictive process using smart decision making [ 13 , 14 ]. For fault detection in fermented beverages, previous research has shown high accuracy for artificial intelligence (AI) tools using NIR, e-noses, and machine learning for beer [ 15 ]. Specifically, Gonzalez Viejo et al [ 15 ] developed a method to detect 18 different faults in beer using a low-cost e-nose coupled with artificial neural networks; this technique is able to predict the level of concentration of faults and the specific compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In related research by Rodman et al [15], the aim has been to gain insight into the brewing process and provide an investigation into the influence of byproduct (diacetyl and ethyl acetate) threshold levels on obtainable fermentation performance by computing optimal operating temperature profiles for a range of constraint levels on byproduct concentrations in the final product. Some recent research has also been exploring faults detection in beers using artificial intelligence methods, as well as using strain development methodology to breed industrial brewing yeast [16,17].…”
Section: Related Workmentioning
confidence: 99%
“…This method uses independent sets of samples for each stage and evaluates the overall accuracy by including all samples. A similar data division to develop ANN models was used in previous studies [35,59,74]. Besides, several retraining attempts were conducted to assess the consistency of the results, obtaining similar results in every attempt.…”
Section: Machine Learning Modelingmentioning
confidence: 99%
“…The artificial neural networks (ANNs) for supervised ML are well-known for solving multiclass classifications due to their ability to deal with non-linear data for pattern recognition to obtain high accuracy. For example, the ANN models were used in previous studies to classify mulberry fruit according to the ripeness levels [27], detect beer faults using the electronic nose [35], and classify aphid infestation levels using the electronic nose and near-infrared spectroscopy [36].…”
Section: Introductionmentioning
confidence: 99%